A clinical study of type 1 neurofibromatosis in north west England. Issue 3 (1st March 1999) - McGaughran, J M; Harris, D I; Donnai, D; Teare, D; MacLeod, R; Westerbeek, R; Kingston, H; Super, M; Harris, R; Evans, D G R
Abstract : A clinical study of patients on the North West Regional Genetic Register with neurofibromatosis type 1 (NF1) identified 523 affected cases from 304 families. In those for whom relevant information was available, 86.7% (383 of 442) had more than six café au lait patches, 83.8% (310 of 370) had axillary freckling, 42.3% (151 of 357) had inguinal freckling, and 63% (157 of 249) had Lisch nodules. Cutaneous neurofibromas were present in 59.4% (217 of 365) and 45.5% (150 of 330) were noted to have subcutaneous tumours. Plexiform neurofibromas were present in 15.3% (80 of 523). A positive family history of NF1 was found in 71.2% (327 of 459) and 28.8% (132 of 459) of affected patients were considered to be the result of a new mutation. Learning difficulties of varying severity occurred in 62% (186 of 300). CNS tumours associated with NF1 were reported in 9.4% (49) of patients, optic gliomas occurring in 25 of these, 4.8% of patients. Some degree of scoliosis was reported for 11.7% (61), 1.9% (10) had pseudoarthrosis, 4.3% (23) had epilepsy, and 2.1% (11) had spinal neurofibromas. Actuarial analyses were carried out for both optic glioma and malignant nerve sheath tumours and the data are presented.